Sociality and tattoo skin disease among bottlenose dolphins in Shark Bay, Australia. (24th December 2019) - Powell, Sarah N; Wallen, Megan M; Miketa, Madison L; Krzyszczyk, Ewa; Foroughirad, Vivienne; Bansal, Shweta; Mann, Janet
Abstract: Social behavior is an important driver of infection dynamics, though identifying the social interactions that foster infectious disease transmission is challenging. Here we examine how social behavior impacts disease transmission in Indo-Pacific bottlenose dolphins ( Tursiops aduncus ) using an easily identifiable skin disease and social network data. We analyzed tattoo skin disease (TSD) lesions based on photographs collected as part of a 34-year longitudinal study in relation to the sociality of T. aduncus using three metrics (degree, time spent socializing, and time in groups) and network structure, using the k -test. We show that calves with TSD in the second year of life associated more with TSD-positive individuals in the first year of life compared with calves that did not have TSD. Additionally, the network k -test showed that the social network links are epidemiologically relevant for transmission. However, degree, time spent in groups, and time spent socializing were not significantly different between infected and uninfected groups. Our findings indicate that association with infected individuals is predictive of an individual's risk for TSD and that the social association network can serve as a proxy for studying the epidemiology of skin diseases in bottlenose dolphins. Abstract : Social behavior is an important factor in disease spread, yet wildlife epidemiological studies often lack data either on the disease or the social network. Using social network and disease data from a 34-year longitudinal study, we found that association with symptomatic individuals increased the risk of later contracting the disease. This study shows that associating with symptomatic individuals proved to be a better predictor of disease than rates of social interaction overall.